Binary dirty paper coding - Castanheira, D. (2010)
This paper proposes a practical scheme for implementing binary dirty paper coding (DPC) using a low density generator matrix code (LDGM) concatenated with a high rate low density parity check (LDPC) code. We also propose a new algorithm, a modified version of the belief propagation algorithm (BP), for doing lossy source coding at the encoder, with linear complexity in the block length. In contrast to the superposition coding framework, where high order alphabet codes are used, we propose to implement binary DPC using only binary codes. Through application of approximate density evolution and linear programming we optimize the degree distribution of the proposed code. Simulation results show that our scheme achieves close to state-of-the-art performance with reduced complexity.